2010
DOI: 10.1371/journal.pone.0014465
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Object Categories from Event-Related EEG: Toward Decoding of Conceptual Representations

Abstract: Multivariate pattern analysis is a technique that allows the decoding of conceptual information such as the semantic category of a perceived object from neuroimaging data. Impressive single-trial classification results have been reported in studies that used fMRI. Here, we investigate the possibility to identify conceptual representations from event-related EEG based on the presentation of an object in different modalities: its spoken name, its visual representation and its written name. We used Bayesian logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
147
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(167 citation statements)
references
References 86 publications
(90 reference statements)
19
147
1
Order By: Relevance
“…The phase bifurcation effect in this time-frequency range had anterior-parietal topography with the top value at channel POz (Simanova et al 2010) which was reported connecting with N170. The white marker in Fig.…”
Section: Results Of the Phase Bifurcation Indexsupporting
confidence: 62%
“…The phase bifurcation effect in this time-frequency range had anterior-parietal topography with the top value at channel POz (Simanova et al 2010) which was reported connecting with N170. The white marker in Fig.…”
Section: Results Of the Phase Bifurcation Indexsupporting
confidence: 62%
“…Using electrophysiologic signals, decoding sound categories at the single-trial AEP level has turned out to be more challenging than in the visual domain. Simanova et al (Simanova et al, 2010) attempted at decoding semantic categories of auditory stimuli at the single-trial level in an experiment in which subjects were asked to perform a task irrelevant to the categorization. A multivariate pattern analysis based on Bayesian logistic regression performed poorly in comparison to a similar analysis applied to visual stimuli; and in about half of the subjects they obtained chance-level classification accuracy.…”
Section: Multivariate Decodingmentioning
confidence: 99%
“…Here, a popular paradigm involves discriminating the direction of motion of a field of moving dots (Bennur and Gold, 2011;Britten et al, 1992;Kim and Shadlen, 1999;Newsome et al, 1989;Shadlen and Newsome, 1996) during which activity in area MT could predict motion discrimination, whereas activity in the lateral intraparietal area (LIP), the frontal eye-field (FEF) and the dorsolateral prefrontal cortex (DLPFC) was directly related to forming the decision. More recently, perceptual decision-making in the visual domain has been investigated with complex stimuli and tasks involving perceptual and semantic categorization (Murphy et al 2011;Ratcliff et al, 2009;Simanova et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Developmental studies show that perceptual categorization develops during the first months of life (Mandler, 2004), and multiple neuroimaging studies have reported differential activation for stimuli from different semantic domains (Mahon & Caramazza, 2009;Gerlach, 2007;Martin & Chao, 2001;Chao & Martin, 2000;Chao, Haxby, & Martin, 1999;Caramazza & Shelton, 1998;Martin, Wiggs, Ungerleider, & Haxby, 1996;Perani et al, 1995). More recent research has demonstrated that the semantic category or entity of an object can be successfully predicted from neural activity patterns when the object is presented visually (Murphy et al, 2011;Reddy & Kanwisher, 2007;Haynes & Rees, 2006;Kamitani & Tong, 2005;Cox & Savoy, 2003;Haxby et al, 2001) or orthographically (Simanova, Hagoort, Oostenveld, & van Gerven, 2014;Chan, Halgren, Marinkovic, & Cash, 2011;Murphy et al, 2011;Shinkareva, Malave, Mason, Mitchell, & Just, 2011;Simanova, van Gerven, Oostenveld, & Hagoort, 2010). It can be argued, however, that the use of visual or orthographical stimuli in these tasks introduce confounding visual or phonological effects related to semantic retrieval (Hwang, Palmer, Basho, Zadra, & Müller, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It can be argued, however, that the use of visual or orthographical stimuli in these tasks introduce confounding visual or phonological effects related to semantic retrieval (Hwang, Palmer, Basho, Zadra, & Müller, 2009). An additional concern, more specific to visual stimulus presentation, is that certain perceptual attributes that are different between categories can bias the decoding outcome ( Vindiola & Wolmetz, 2011;Simanova et al, 2010). It is possible to minimize these confounds by using an internally guided word generation task, without presenting any pictures or words to participants.…”
Section: Introductionmentioning
confidence: 99%